The Long-term Outcome of Primary "Bleb-sparing, Epithelial Exchange" in Dysfunctional Filtering Blebs. Issue 7 (July 2016) - Sihota, Ramanjit; Angmo, Dewang; Sen, Seema; Gupta, Viney; Dada, Tanuj; Pandey, Ravindra M.
Abstract : Objective: To evaluate the long-term outcome of epithelial peeling and conjunctival replacement as a primary procedure in dysfunctional filtering blebs, without excising the bleb. Materials and Methods: A prospective, observational case series involving 34 consecutive eyes, having prior operated trabeculectomy with a dysfunctional filtering bleb, that met the inclusion criteria and were reviewed for at least 12 months. The bleb epithelium was peeled off and replaced with the adjacent conjunctiva, without bleb excision. Patients were reviewed at 1 week, 1 and 3 months postoperatively, and thereafter every 6 months for best corrected visual acuity (BCVA), applanation tonometry, bleb morphology and leaks, the lens status, glaucoma medications, and any complications. ASOCT was performed preoperatively and at the last review. Complete success (primary outcome) was defined as an intraocular pressure (IOP) >6 and <18 mm Hg without any additional antiglaucoma medications at the last follow-up. Results: The average age of the patients was 36.6±20.7 years. The average time of follow-up was 23.9±6.1 months (range, 13 to 40 mo). The mean preoperative IOP was 5.8±4.2 mm Hg. Postoperatively, the IOP at 24 months was 12.6±3.9 mm Hg ( P <0.0001). The bleb characteristics were graded according to the Indiana Bleb Appearance Grading Scale (IBAGS), which showed significant results in terms of the height (H), the vascularity (V), and Seidel (S) ( P <0.0001). The preoperative and the postoperative BCVAs in logMAR were 0.51±0.26 and 0.37±0.21 ( P =0.0001), respectively. Complete success was noted in 31/34 eyes (91.18%) and qualified success was noted in 3 eyes (8.82%). One patient developed a mild ptosis after bleb revision. Conclusions: Epithelial peeling of the bleb with replacement by advancement, without bleb excision, maintains bleb function and resolves bleb dysfunction in the long term. Abstract : Supplemental Digital Content is available in the text.